DEBATE ATUAL SOBRE O GNOSTICISMO: UM OLHAR SOBRE O JESUS GNÓSTICO DE NAG HAMMADI - Amadeu, Antero Luiz (2010)
The encounter between Christianity and Greek culture was one of the greatest events in human history. This event allowed the expansion of Christianity beyond its homeland since the first century AD. In little time, Christianity was able to establish itself in several locations throughout the ancient world. This shift led its division into separate sections, each trusting Jesus in their own way. The one which was projected into North Africa fostered a type of Christianity with Gnostic traces. That possibility came to light from some writings found in this region in the mid-twentieth century and that was also attributed to that Christian part. This research has as its objective to analyze this Christian bias based on these findings. This group, considered a minority, had some claims on the official Christianity that regarded them as heretics. The researched target was the way the Gnostics saw Jesus since they considered themselves Christians.